Optimization of lipase-catalyzed synthesis of N-trans-feruloyltyramine using response surface methodology (RSM) - Basri, Mahiran; Alrub, Mohammad Abu; Abd Malek, Emilia; Alang Ahmad, Shahrul Ainliah; Salleh, Abu Bakar; Abdul Rahman, Mohd Basyaruddin (Taylor & Francis, 2014)
Enzymatic synthesis of N-trans-feruloyltyramine amide was optimized by response surface methodology (RSM) using 4-hydroxy-3-methoxycinnamic acid and tyramine hydrochloride in a one-step lipase catalyzed reaction using Lipozyme TL IM. Response surface methodology (RSM) based on five-level, four-variable central composite rotatable design (CCRD) was used to evaluate the interaction of synthesis, reaction time (24–96 h), temperature (30°–50°C), amount of enzyme (50–500 mg, 12.5–125.0 IUN), and substrate molar ratio (cinnamic acid:tyramine HCl) 1:1–8:1 mmol on the percentage yield of N-trans-feruloyltyramine amide. The optimum conditions derived via RSM were: reaction time 52 h, temperature 43°C, amount of enzyme 260 mg (65.0 IUN), and substrate molar ratio (cinnamic acid:tyramine HCl) 6.2:1. The actual experimental yield was 96.3% under optimum conditions, which compared well to the maximum predicted value of 97.2%.